Frontiers in medical physics: material classification and blood pressure measurement of wearable piezoelectric sensors - Cao, Fuchen; Li, Yanli (Frontiers in Physics, 2024)
Wearable piezoelectric sensors, as an emerging tool for blood pressure measurement, have attracted much attention at the forefront of medical physics and have broad application prospects due to their portability, real-time monitoring and low interference with human activities. However, the development of piezoelectric materials is currently a key factor restricting the development of wearable piezoelectric sensors. In order to continuously improve the accuracy and speed of blood pressure measurements by wearable piezoelectric sensors, new measurement methods need to be designed in addition to the development of high-performance piezoelectric materials. We present the advantages and disadvantages of different types of piezoelectric materials for wearable piezoelectric sensors, illustrate their future development directions, and discuss the current new strategies and the latest applied research of piezoelectric sensors applied to blood pressure measurement. In addition, the challenges and future prospects of wearable piezoelectric sensors for blood pressure measurement are revealed, providing new ideas for future applications of high-performance wearable piezoelectric sensors for health monitoring.